Pengaruh Latihan Ujjayi Pranayama dalam Meningkatkan Kepercayaan Diri Siswa pada Usia Remaja - Ni Luh Pitya Ulansari; I Gusti Made Widya Sena (UHN IGB Sugriwa Denpasar, 2021)
Students who are still teenagers are a transitional period from children to adults, where in this phase they are adolescents with very high egos and can affect how they see the world. But this is also a concern in itself, where some of them are too closed themselves and lack self-confidence. Because they are too afraid and anxious about how others think of them, they are reluctant to show themselves. Various literature and research shows that going through pranayama can psychologically affect and calm one's anxiety. The purpose of this journal is to describe pranayama in increasing self-confidence. The method used is a literature study by entering the keywords youth, self-confidence and Pranayama at google.scholar.com. In this journal, it is explained that pranayama can increase students' self-confidence in their teens. The purpose of pranayama is to relax the mind so that it can get rid of anxiety. Of course this will help students increase their self-confidence.